2008
DOI: 10.1128/jvi.02233-07
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Inactivation of Influenza Viruses Confers Preservation of Viral Structure with Enhanced Immunogenicity

Abstract: The use of inactivated influenza virus for the development of vaccines with broad heterosubtypic protection requires selective inactivation techniques that eliminate viral infectivity while preserving structural integrity. Here we tested if a hydrophobic inactivation approach reported for retroviruses could be applied to the influenza virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…4). These results corroborated our previous findings with V3000 strain of VEEV [26] and also with other reports of inactivation of influenza, Ebola, HIV and SIV viruses by INA [31][32][33]. Further RNA isolated from the INA-inactivated V3526 did not show any infectivity (Supplementary Fig.…”
Section: Group(s)supporting
confidence: 82%
See 2 more Smart Citations
“…4). These results corroborated our previous findings with V3000 strain of VEEV [26] and also with other reports of inactivation of influenza, Ebola, HIV and SIV viruses by INA [31][32][33]. Further RNA isolated from the INA-inactivated V3526 did not show any infectivity (Supplementary Fig.…”
Section: Group(s)supporting
confidence: 82%
“…Adjuvants such as CpG and Alhydrogel have been shown to enhance the antibody titers and protection in mice immunized with gamma irradiated V3526 [41]. These results are similar to those demonstrated by others with influenza and Ebola viruses where INA-inactivated viruses induced protective antibody response to respective viruses [32,33]. We also demonstrate in vitro that INA can efficiently inactivate the live attenuated vaccine strain V3526 of VEEV.…”
Section: Group(s)supporting
confidence: 75%
See 1 more Smart Citation
“…However, the antibodies induced were generally 3-fold lower compared with that induced by live virus. 35 In contrast, we have shown that dengue-2 virus inactivated by AMT retained the ability to bind to all tested monoclonal antibodies. Although dengue virus type 1 inactivation and immunogenicity was reported previously 33,34 a comparison with other methods of inactivation, including formaldehyde inactivation has not been previously made.…”
Section: Discussionmentioning
confidence: 78%
“…Iodonaphthyl azide (INA) has also been used as an agent for photochemical inactivation of viruses. 22,35,36 While psoralen derivatives target pyrimidines in 22 It is not clear why INA-inactivated dengue-2 virus bound monoclonal antibodies less well compared with live virus. Intra-nasal immunization of mice with influenza virus similarly inactivated using INA induced antibodies and protected mice from live virus challenge.…”
Section: Discussionmentioning
confidence: 99%